2011
DOI: 10.1007/s00420-011-0678-8
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in a cohort of cement workers in a plant of Central Italy

Abstract: Portland cement workers had a statistically significant reduced risk of overall mortality and of all cancers mortality probably due to the healthy workers effect. The study confirmed an increased risk of respiratory system cancer only in the subgroup with previous work exposure in a cement/asbestos plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…For lung cancer mortality, the pattern of SMRs was similar to that seen for all cancers with four of the seven studies reporting SMRs with CIs overlapping the null, two studies showing slightly decreased SMRs (SMR=0.53, 95% CI 0.27 to 0.95)12 and (SMR=0.56, 95% CI 0.32 to 0.89),6 and one reporting an increase for lung cancer (n=85 cases; PMR=2.05, 95% CI 1.65 to 2.627; figure 2). The meta-SMR for lung cancer mortality was 0.93 (95% CI 0.62 to 1.39).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…For lung cancer mortality, the pattern of SMRs was similar to that seen for all cancers with four of the seven studies reporting SMRs with CIs overlapping the null, two studies showing slightly decreased SMRs (SMR=0.53, 95% CI 0.27 to 0.95)12 and (SMR=0.56, 95% CI 0.32 to 0.89),6 and one reporting an increase for lung cancer (n=85 cases; PMR=2.05, 95% CI 1.65 to 2.627; figure 2). The meta-SMR for lung cancer mortality was 0.93 (95% CI 0.62 to 1.39).…”
Section: Resultssupporting
confidence: 52%
“…Half of the studies of all cancers combined reported CIs overlapping the null5 10 12 while two others showed slightly decreased SMRs for all cancers for cement workers (SMR=0.80, 95% CI 0.69 to 0.92)8 and (SMR=0.64, 95% CI 0.48 to 0.82),6 and one showed a slight increase (PMR=1.30, 95% CI 1.13 to 1.49) 7. The meta-SMR for all cancers combined was 0.94 (95% CI 0.76 to 1.16).…”
Section: Resultsmentioning
confidence: 99%
“…Dab and colleagues, in a French cohort study with a follow up period of 15 years, also failed to demonstrate an elevated mortality from respiratory cancer among workers of a cement industrial plant [9]. Giordano et al, in an Italian cohort study, found a significantly elevated mortality for respiratory cancer, exclusively in a group of cement workers with previous exposure to asbestos [10]. On the other hand, Smailyte and coworkers in a cohort study among workers of the Lithuanian cement industry plan, found an excess in Standardised Mortality Ratio (SMR) for lung cancer [7].…”
Section: Discussionmentioning
confidence: 99%
“…There is contradictory evidence of an association between exposure to cement dust and lung function impairment [3,4]. This is also the case for the association between exposure to cement dust and respiratory tract malignancies, in particular lung and larynx cancer [5-10]. Nevertheless, it is notable that almost all studies evaluating the association between cement dust and respiratory cancer have included subjects from one or two cement factories, resulting in a low generalizability of the observed results.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the volatility of cement dust, the main targets in the human body are the respiratory system, skin, and eyes. It has been reported that cement dust in work environments are associated with a higher prevalence of chronic respiratory symptoms and reduced lung function [10][11][12]; however, no difference in mortality rates was seen in a cohort study of cement workers in a plant in Central Italy [20]. Furthermore, a recent survey found that cement workers were at a higher risk of developing COPD (prevalence of 18.8%) than the administrative workers of the same factory (prevalence of 4.8%), independent of smoking habits [21].…”
Section: Discussionmentioning
confidence: 89%